Pengaruh Indeks Pembangunan Manusia (IPM), Kemiskinan dan Pengangguran Terhadap Pertumbuhan Ekonomi di Provinsi Jawa Timur - Agung Aji Ramdani; Amira Zaimatun Nisa; Yasiska Cahya Rachmawati; Dewi Rohma Wati (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to identify the influence of the Human Development Index (HDI), poverty level, and unemployment rate on economic growth in East Java Province for the period 2003–2023. This research data comes from the official publication of the Central Statistics Agency (BPS) of East Java and Indonesia, using secondary data. The method applied is a quantitative approach with multiple linear regression analysis supported by classical assumption testing to ensure the validity of the analysis model. The results of the analysis show that HDI and poverty levels have a significant negative influence on economic growth, with regression coefficients of -0.248 and -0.163 respectively. On the other hand, the unemployment rate has a significant positive influence on economic growth with a coefficient of 0.351 which reflects the existence of structural economic transformation. Overall, these variables explain 52.8% of the variation in economic growth, while the remainder is influenced by other factors not examined in this study. It is hoped that these findings can become a basis for formulating more inclusive and sustainable policies.